F. Scott Barker's Access 2002 power programming - Barker, F. Scott (Sams, 2002)
F. Scott Barker's Access 2002 Power Programming gives many practical techniques for the corporate and independent developer. The main topics covered are: The Root of Power Programming; Manipulating and Presenting Data; Extending Access with Interoperability; Adding the Professional Look and Distributing Applications; Managing Databases; Adding Finishing Touches. New features of Access 2002 will be covered thoroughly, including: A whole new chapter devoted to Data Pages, which is Microsoft's way of bringing the Web interface into everyday office solutions. A new chapter clarifying the confusion over ADP/MDB and DAO/ADO. Including when and where to use each. There are a number of new additions to VBA which developers will need good exposure to in order to take advantage of them. A number of changes have been implemented in the form design with control features added.